Water treatment nanofiltration membrane capable of removing hardness and preparation method

By using a non-woven support layer, a microporous ultrafiltration layer and a separation functional layer composed of furfural and melamine copolymerized crosslinking resin in the nanofiltration membrane, the problem that the existing nanofiltration membrane cannot withstand strong acids and strong alkalis is solved, and efficient removal of calcium and magnesium ions is achieved, reducing the processing cost and complexity.

CN119612689AActive Publication Date: 2025-03-14JIANGSU BANGTEC ENVIRONMENTAL SCI TECH CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411961802.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-03-14
Estimated Expiration
2044-12-30

AI Technical Summary

Technical Problem

The existing nanofiltration membranes cannot withstand strong acids, strong alkalis and strong oxidation environments, resulting in the need of complex pretreatment processes in photovoltaic wastewater treatment, which increases the cost and complexity of treatment.

Method used

A nanofiltration membrane structure with a non-woven fabric as the support layer and a microporous ultrafiltration layer as the base membrane, and a separation functional layer is coated on the surface of the base membrane. The separation functional layer is composed of furfural and melamine, or a copolymer crosslinking resin of furfural, melamine and formaldehyde, which can withstand strong acid and strong alkali environments and effectively intercept calcium and magnesium ions.

Benefits of technology

The long-term performance stability of the nanofiltration membrane in a strong acid, strong alkali and strong oxidation environment is achieved, and the removal rate of calcium and magnesium ions is significantly improved, reducing the risk of scaling, and is suitable for dehardening water quality in photovoltaic wastewater treatment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119612689A_ABST
    Figure CN119612689A_ABST
Patent Text Reader

Abstract

The invention discloses a water treatment nanofiltration membrane capable of removing hardness. The water treatment nanofiltration membrane is characterized in that non-woven fabric is used as a supporting layer; the microporous ultrafiltration layer is used as a base membrane; the surface of the base membrane is coated with the separation function layer. The invention also discloses a preparation method of the water treatment nanofiltration membrane capable of removing hardness, if the separation function layer is composed of furfural and melamine copolymerized cross-linked resin, the preparation method comprises the following steps: S1, mixing furfural and melamine according to a certain ratio to prepare an aqueous solution with the concentration range of 1-10%, and adding 1-10% of a catalyst into the aqueous solution to prepare a final solution; s2, uniformly coating the final solution on the surface of an ultrafiltration bottom die; and S3, controlling the heating temperature to be 60-120 DEG C, and performing cross-linking curing and drying on the coating to form a stable separation functional layer. The invention also discloses a preparation method of the water treatment nanofiltration membrane for removing hardness. The method is resistant to strong acid and strong alkali, and calcium and magnesium ions can be effectively intercepted.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a water treatment nanofiltration membrane for removing hardness and a preparation method thereof. Background Art

[0002] The photovoltaic production process involves a large number of chemical cleaning, etching, acid-base adjustment and other processes, which will produce wastewater containing heavy metals, acids, alkalis, solvents and other harmful substances. If these wastewaters are discharged directly without treatment, they will cause serious pollution to the environment. Therefore, the use of membrane technology for photovoltaic wastewater treatment has become an effective solution. In the process of photovoltaic wastewater treatment, calcium carbonate is often added to remove fluoride ions. Calcium ions will increase the hardness of water quality, greatly increasing the scaling risk of subsequent membrane treated water reuse. Removing hardness from water has become a key link in photovoltaic wastewater treatment. Nanofiltration membrane, as an efficient separation technology, can effectively remove calcium, magnesium and other ions in water, effectively reduce water hardness, reduce scaling risks, and ensure the purity of recycled water quality. With the continuous development of nanofiltration membrane technology, membrane materials for removing calcium ions from photovoltaic wastewater are gradually developing towards high efficiency, durability and low cost, showing broad application prospects.

[0003] However, the separation layer of the nanofiltration membranes currently available on the market is mainly based on a polyamide structure, which is intolerant to strong acid, strong alkali and strong oxidizing environments. In order to ensure long-term performance stability, the concentration of oxidizing substances in the inlet water is required to be less than 0.1ppm, the acid concentration is less than 0.2%, and the alkali concentration is less than 0.004%. Due to the special characteristics of photovoltaic wastewater, such as strong acid, concentrated alkali and high oxidation, conventional nanofiltration membranes cannot be used directly and require a complex pretreatment process, which increases the processing cost.

[0004] Therefore, a water treatment nanofiltration membrane capable of withstanding strong acids and alkalis and removing hardness and a preparation method thereof are provided. Summary of the invention

[0005] The purpose of the present invention is to overcome the existing defects and provide a water treatment nanofiltration membrane for removing hardness and a preparation method, which is resistant to strong acids and strong bases and can effectively intercept calcium and magnesium ions.

[0006] The technical solution to achieve the above purpose is: One of the present invention is a water treatment nanofiltration membrane for removing hardness, comprising: Using non-woven fabric as the support layer; Using a microporous ultrafiltration layer as a base membrane; and The separation functional layer is coated on the surface of the base membrane.

[0007] Preferably, the material of the non-woven fabric includes but is not limited to polypropylene, polypropylene ethylene and polyphenylene sulfide.

[0008] Preferably, the microporous ultrafiltration layer material includes but is not limited to polysulfone, polyethersulfone, polyethylene, polypropylene and polyvinylidene fluoride, wherein the micropore diameter is between 3-30 nanometers and the ultrafiltration layer thickness is between 5-50 micrometers.

[0009] Preferably, the separation functional layer has a thickness of 1-100 nanometers, and its structure is composed of a copolymer cross-linked resin of furfural and melamine, wherein the molar ratio of furfural to melamine is in the range of 1:1 to 5:1.

[0010] Preferably, the separation functional layer has a thickness of 1-100 nanometers and a structure composed of a copolymer cross-linked resin of furfural, melamine and formaldehyde, wherein the molar ratio of furfural to melamine is in the range of 1:1 to 5:1, and the molar ratio of formaldehyde to melamine is in the range of 4:1 to 2:1.

[0011] The second method of the present invention is a method for preparing a water treatment nanofiltration membrane for removing hardness. If the separation functional layer is composed of a copolymerized cross-linked resin of furfural and melamine, the preparation method comprises: Step S1, furfural and melamine are mixed in a certain proportion to prepare an aqueous solution with a concentration range of 1%-10%, and 1-10% of a catalyst is added to the aqueous solution to obtain a final solution; Step S2, evenly coating the final solution on the surface of the ultrafiltration bottom mold; Step S3, controlling the heating temperature between 60-120° C., the coating is cross-linked, cured and dried to form a stable separation functional layer.

[0012] Preferably, in step S1, the catalyst is a strong acid or a Lewis acid, wherein the strong acid includes but is not limited to sulfuric acid, benzenesulfonic acid and trifluoroformic acid, and the Lewis acid includes but is not limited to zinc nitrate and aluminum nitrate.

[0013] Preferably, in step S2, the ultrafiltration bottom mold is composed of a non-woven fabric as a support layer and a microporous ultrafiltration layer as a base membrane; In the step S2, the coating method is one of dipping, spraying, printing, transfer, and slit coating.

[0014] The third method of the present invention is a method for preparing a water treatment nanofiltration membrane for removing hardness. If the separation functional layer is composed of a copolymerized cross-linked resin of furfural, melamine and formaldehyde, the preparation method comprises: Step S4, furfural, melamine and formaldehyde are mixed in a certain proportion to prepare an aqueous solution with a concentration range of 1%-10%, and an appropriate amount of sodium hydroxide is added to the aqueous solution to adjust the solution; Step S5, heating at 80° C. for 10-20 hours and then cooling to room temperature, adding 1-10% of a catalyst to the resulting solution to obtain a final solution; Step S6, evenly coating the final solution on the surface of the ultrafiltration bottom mold; Step S7, controlling the heating temperature between 60-120° C., the coating is cross-linked, cured and dried to form a stable separation functional layer.

[0015] Preferably, in step S4, the pH value of the solution is adjusted to 9-10; In step S5, the catalyst is a strong acid or a Lewis acid, wherein the strong acid includes but is not limited to sulfuric acid, benzenesulfonic acid and trifluoroformic acid, and the Lewis acid includes but is not limited to zinc nitrate and aluminum nitrate; In step S6, the ultrafiltration bottom mold is composed of a non-woven fabric as a support layer and a microporous ultrafiltration layer as a base membrane; In the step S6, the coating method is one of dipping, spraying, printing, transfer, and slit coating.

[0016] The beneficial effects of the present invention are as follows: the present invention uses non-woven fabric as a support layer, selects non-woven fabric materials resistant to strong acids and alkalis, uses a microporous ultrafiltration layer as a base membrane, and selects acid-base resistant materials, so that the nanofiltration membrane can withstand strong acids, strong alkalis and strong oxidation environments, thereby ensuring the long-term performance stability of the nanofiltration membrane. The separation functional layer structure coated on the surface of the base membrane is composed of furfural and melamine, or furfural, melamine and formaldehyde, and the performance of removing calcium and magnesium ions is greatly improved, which can effectively intercept calcium and magnesium ions. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 It is a flow chart of a method for preparing a water treatment nanofiltration membrane for removing hardness according to the present invention; Figure 2 is another flow chart of a method for preparing a water treatment nanofiltration membrane for removing hardness according to the present invention; Figure 3 is a chemical structure diagram of furfural in the present invention; Figure 4 It is the chemical structure diagram of melamine in the present invention. DETAILED DESCRIPTION

[0018] The technical solution of the present invention will be described clearly and completely below in conjunction with the accompanying drawings. In the description of the present invention, it should be noted that the terms "center", "up", "down", "left", "right", "vertical", "horizontal", "inside", "outside" and the like indicate directions or positional relationships based on the directions or positional relationships shown in the accompanying drawings, which are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific direction, be constructed and operated in a specific direction, and therefore cannot be understood as a limitation on the present invention. In addition, the terms "first", "second", and "third" are used for descriptive purposes only and cannot be understood as indicating or implying relative importance.

[0019] The present invention will be further described below in conjunction with the accompanying drawings.

[0020] A water treatment nanofiltration membrane for removing hardness comprises: a non-woven fabric as a support layer; a microporous ultrafiltration layer as a base membrane; and a separation function layer coated on the surface of the base membrane.

[0021] In the embodiment, the material of the non-woven fabric includes but is not limited to polypropylene, polypropylene ethylene and polyphenylene sulfide.

[0022] In the embodiment, the material of the microporous ultrafiltration layer includes but is not limited to polysulfone, polyethersulfone, polyethylene, polypropylene and polyvinylidene fluoride, wherein the micropore diameter is between 3-30 nanometers and the thickness of the ultrafiltration layer is between 5-50 micrometers.

[0023] In the embodiment, the separation functional layer has a thickness of 1-100 nanometers and a structure composed of a copolymer cross-linked resin of furfural and melamine, wherein the molar ratio of furfural to melamine is in the range of 1:10 to 10:1, preferably 1:1 to 5:1, and furfural can be replaced by furfuryl alcohol. The chemical structure of furfural is as follows: Figure 3 As shown, the chemical structure of melamine is Figure 4 shown.

[0024] In an embodiment, the separation functional layer has a thickness of 1-100 nanometers, and its structure is composed of a copolymer cross-linked resin of furfural, melamine and formaldehyde, wherein the molar ratio of furfural to melamine is in the range of 1:10 to 10:1, preferably 1:1 to 5:1, and the molar ratio of formaldehyde to melamine is in the range of 4:1 to 2:1.

[0025] like Figure 1 As shown, a method for preparing a water treatment nanofiltration membrane for removing hardness, if the separation functional layer is composed of a copolymer cross-linked resin of furfural and melamine, the preparation method comprises: Step S1, furfural and melamine are mixed in a certain proportion to prepare an aqueous solution with a concentration range of 1%-10%, and 1-10% of a catalyst is added to the aqueous solution to obtain a final solution.

[0026] In the embodiment, the catalyst is a strong acid or a Lewis acid, wherein the strong acid includes but is not limited to sulfuric acid, benzenesulfonic acid and trifluoroformic acid, and the Lewis acid includes but is not limited to zinc nitrate and aluminum nitrate.

[0027] Step S2, evenly coating the final solution on the surface of the ultrafiltration bottom mold.

[0028] In the embodiment, the ultrafiltration bottom mold is composed of a non-woven fabric as a support layer and a microporous ultrafiltration layer as a base membrane.

[0029] In the embodiment, the coating method is one of dipping, spraying, printing, transfer, and slit coating.

[0030] Step S3, controlling the heating temperature between 60-120° C., the coating is cross-linked, cured and dried to form a stable separation functional layer.

[0031] like Figure 2 As shown, a method for preparing a water treatment nanofiltration membrane for removing hardness, if the separation functional layer is composed of a copolymer cross-linked resin of furfural, melamine and formaldehyde, the preparation method comprises: Step S4, furfural, melamine and formaldehyde are mixed in a certain proportion to prepare an aqueous solution with a concentration range of 1%-10%, and a proper amount of sodium hydroxide is added to the aqueous solution to adjust the solution.

[0032] In the embodiment, the pH value of the solution is adjusted to 9-10.

[0033] Step S5, heating at 80° C. for 10-20 hours and then cooling to room temperature, adding 1-10% of a catalyst to the resulting solution to obtain a final solution.

[0034] In the embodiment, the catalyst is a strong acid or a Lewis acid, wherein the strong acid includes but is not limited to sulfuric acid, benzenesulfonic acid and trifluoroformic acid, and the Lewis acid includes but is not limited to zinc nitrate and aluminum nitrate.

[0035] Step S6, evenly coating the final solution on the surface of the ultrafiltration bottom mold.

[0036] In the embodiment, the ultrafiltration bottom mold is composed of a non-woven fabric as a support layer and a microporous ultrafiltration layer as a base membrane.

[0037] In the embodiment, the coating method is one of dipping, spraying, printing, transfer, and slit coating.

[0038] Step S7, controlling the heating temperature between 60-120° C., the coating is cross-linked, cured and dried to form a stable separation functional layer.

[0039] The comparative examples and Examples 1-4 illustrate that the scheme of the present invention can effectively improve the effect of nanofiltration membrane in removing hardness.

[0040] Comparative Example: Mix 8.0g furfuryl alcohol and 2.5g formaldehyde in 89.5g pure water, slowly add 50% NaOH solution to adjust the solution pH between 9.5-10, heat the solution at 80℃ for 10 hours, and cool to room temperature. Add 5g trifluoroacetic acid to make a coating solution. The surface of the polysulfone ultrafiltration bottom membrane (pore size 10nm, thickness 30um, polypropylene non-woven fabric support layer) is evenly coated with the above coating solution, enters a 100℃ oven for cross-linking polymerization reaction, and the residence time is 180 seconds, and then soaked in pure water to wash until the pH is neutral. The obtained membrane is tested for calcium chloride separation performance, the test pressure is 100psi, the concentration of calcium chloride aqueous solution is 500ppm, the membrane surface flow rate is>4L / min, and after stabilization for 30min, the flux is measured to be 20LMH, and the calcium chloride removal rate is 8.5%.

[0041] Example 1: 8.0g of furfuryl alcohol and 10.3g of melamine were mixed in 81.7g of pure water, and 3.0g of zinc chloride was added to prepare a coating solution. The surface of the polysulfone ultrafiltration bottom membrane was evenly coated with the above solution, and placed in a 120°C oven for cross-linking polymerization reaction, with a residence time of 180 seconds, and then soaked in pure water to wash until the pH was neutral. The obtained membrane was tested for calcium chloride separation performance, with a test pressure of 100psi and a calcium chloride aqueous solution concentration of 500ppm. The measured flux was 16.8LMH, and the calcium chloride removal rate was 62.1%.

[0042] Example 2: 3.0g of furfuryl alcohol and 19.3g of melamine were mixed in 77.7g of pure water, and 3.0g of zinc chloride was added to prepare a coating solution. The surface of the polysulfone ultrafiltration bottom membrane was evenly coated with the above solution, placed in a 120°C oven for cross-linking polymerization reaction, with a residence time of 180 seconds, and then soaked in pure water to wash until the pH was neutral. The obtained membrane was tested for calcium chloride separation performance, with a test pressure of 100psi and a calcium chloride aqueous solution concentration of 500ppm. The measured flux was 9.1LMH, and the calcium chloride removal rate was 85.8%.

[0043] Example 3: 5.0g furfuryl alcohol, 12.8g melamine and 30.6g formaldehyde solution (30%) were mixed into 100g aqueous solution, 50% NaOH solution was slowly added to adjust the pH of the solution to between 9.5-10, and the solution was heated at 80°C for 20 hours and then cooled to room temperature. 5g trifluoroacetic acid was added to prepare a coating solution. The surface of the polysulfone ultrafiltration bottom membrane was evenly coated with the above coating solution, and entered a 100°C oven for cross-linking polymerization reaction, with a residence time of 180 seconds, and then soaked in pure water to wash until the pH was neutral. The obtained membrane was tested for calcium chloride separation performance, with a test pressure of 100psi, a calcium chloride aqueous solution concentration of 500ppm, a measured flux of 7.7LMH, and a calcium chloride removal rate of 80.3%. After the obtained membrane was soaked in a 4% sodium hydroxide aqueous solution for 168 hours, it was washed with pure water until neutral, and its calcium chloride removal rate was tested to be 80.4%, and the performance remained unchanged.

[0044] Example 4: 5.0g furfural, 12.8g melamine and 30.6g formaldehyde solution (30%) were mixed into 100g aqueous solution, 50% NaOH solution was slowly added to adjust the pH of the solution to between 9.5-10, and the solution was heated at 80°C for 20 hours and then cooled to room temperature. 5g trifluoroacetic acid was added to prepare a coating solution. The surface of the polyethylene microporous ultrafiltration bottom membrane (pore size 30nm, thickness 40um, polypropylene non-woven fabric support layer) was evenly coated with the above coating solution, and entered an 80°C oven for cross-linking polymerization reaction, the residence time was 60 seconds, and then soaked in pure water to wash until the pH was neutral. The obtained membrane was tested for calcium chloride separation performance, the test pressure was 100psi, the concentration of calcium chloride aqueous solution was 500ppm, the flux was measured to be 13.8LMH, and the calcium chloride removal rate was 76.1%. After the obtained membrane was soaked in a 4% sodium hydroxide aqueous solution for 168 hours, it was washed with pure water until neutral, and its calcium chloride removal rate was tested to be 76.0%, and the performance remained unchanged.

[0045] From the material perspective, the nanofiltration membrane of the present invention, whether it is the support layer, the ultrafiltration layer or the separation functional layer, can withstand strong acids and concentrated alkalis, is not easily hydrolyzed, and has stable performance. In particular, the removal rate of multivalent cations (such as calcium and magnesium ions) is relatively high. It is suitable for water dehardening and improving the recycling rate of membrane treatment. It has good application prospects in high recovery rate or zero emission wastewater treatment applications.

[0046] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that the technical solutions described in the above embodiments may still be modified, or some or all of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A water treatment nanofiltration membrane for removing hardness, characterized in that: include: Using non-woven fabric as the support layer; Using a microporous ultrafiltration layer as the base membrane; as well as The separation functional layer is coated on the surface of the base membrane.

2. A water treatment nanofiltration membrane for removing hardness according to claim 1, characterized in that: Materials for non-woven fabrics include, but are not limited to, polypropylene, polypropylene ethylene and polyphenylene sulfide.

3. A water treatment nanofiltration membrane for removing hardness according to claim 1, characterized in that: The microporous ultrafiltration layer material includes but is not limited to polysulfone, polyethersulfone, polyethylene, polypropylene and polyvinylidene fluoride, wherein the micropore diameter is between 3-30 nanometers and the ultrafiltration layer thickness is between 5-50 micrometers.

4. A water treatment nanofiltration membrane for removing hardness according to claim 1, characterized in that: The thickness of the separation functional layer is 1-100 nanometers, and the structure is composed of a copolymer cross-linked resin of furfural and melamine, wherein the molar ratio of furfural to melamine is in the range of 1:1 to 5:

1.

5. A water treatment nanofiltration membrane for removing hardness according to claim 1, characterized in that: The thickness of the separation functional layer is 1-100 nanometers, and the structure is composed of a copolymer cross-linked resin of furfural, melamine and formaldehyde, wherein the molar ratio of furfural to melamine is in the range of 1:1 to 5:1, and the molar ratio of formaldehyde to melamine is in the range of 4:1 to 2:

1.

6. A method for preparing a water treatment nanofiltration membrane for removing hardness, characterized in that: If the separation functional layer is composed of a copolymerized cross-linked resin of furfural and melamine, the preparation method thereof comprises: Step S1, furfural and melamine are mixed in a certain proportion to prepare an aqueous solution with a concentration range of 1%-10%, and 1-10% of a catalyst is added to the aqueous solution to obtain a final solution; Step S2, uniformly coating the final solution on the surface of the ultrafiltration bottom mold; Step S3, controlling the heating temperature between 60-120° C., the coating is cross-linked, cured and dried to form a stable separation functional layer.

7. The method for preparing a water treatment nanofiltration membrane for removing hardness according to claim 6, characterized in that: In step S1, the catalyst is a strong acid or a Lewis acid, wherein the strong acid includes but is not limited to sulfuric acid, benzenesulfonic acid and trifluoroformic acid, and the Lewis acid includes but is not limited to zinc nitrate and aluminum nitrate.

8. The method for preparing a water treatment nanofiltration membrane for removing hardness according to claim 6, characterized in that: In step S2, the ultrafiltration bottom mold is composed of a non-woven fabric as a support layer and a microporous ultrafiltration layer as a base membrane; In the step S2, the coating method is one of dipping, spraying, printing, transfer, and slit coating.

9. A method for preparing a water treatment nanofiltration membrane for removing hardness, characterized in that: If the separation functional layer is composed of a copolymerized cross-linked resin of furfural, melamine and formaldehyde, the preparation method thereof comprises: Step S4, furfural, melamine and formaldehyde are mixed in a certain proportion to prepare an aqueous solution with a concentration range of 1%-10%, and an appropriate amount of sodium hydroxide is added to the aqueous solution to adjust the solution; Step S5, heating at 80° C. for 10-20 hours and then cooling to room temperature, adding 1-10% of a catalyst to the resulting solution to obtain a final solution; Step S6, evenly coating the final solution on the surface of the ultrafiltration bottom mold; Step S7, controlling the heating temperature between 60-120° C., the coating is cross-linked, cured and dried to form a stable separation functional layer.

10. The method for preparing a water treatment nanofiltration membrane for removing hardness according to claim 9, characterized in that: In step S4, the pH value of the solution is adjusted to 9-10; In step S5, the catalyst is a strong acid or a Lewis acid, wherein the strong acid includes but is not limited to sulfuric acid, benzenesulfonic acid and trifluoroformic acid, and the Lewis acid includes but is not limited to zinc nitrate and aluminum nitrate; In step S6, the ultrafiltration bottom mold is composed of a non-woven fabric as a support layer and a microporous ultrafiltration layer as a base membrane; In the step S6, the coating method is one of dipping, spraying, printing, transfer, and slit coating.

Citation Information

Patent Citations

  • Preparation method for cross-linking polyvinyl alcohol furfural nanofiltration membrane

    CN101732998A

  • Method for preparing reinforced resin material microsphere

    CN103923289A

  • Preparation method of porous carbon material for efficiently removing dye ions

    CN110479211A

  • Acid-resistant nanofiltration membrane as well as preparation method and application thereof

    CN115672029A

  • Chemical-resistant porous film

    CN1856533A